2003
DOI: 10.1167/iovs.03-0272
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and Phenotypic Preservation of Rabbit Limbal Epithelial Cells on Amniotic Membrane

Abstract: The epithelial cell sheet grown from a limbal explant on amniotic membrane exhibited a phenotype similar to that of the limbus, suggesting that amniotic membrane is a substrate capable of supporting the propagation and preservation of p63-positive limbal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…34 Although the exact mechanism has not been fully elucidated, the 3T3 fibroblast culture system has successfully applied in the limbal epithelial cell culture. [35][36][37][38] Gruenterich et al demonstrated that the addition of 3T3 feeder cells in their cultivation system may be beneficial for preventing limbal epithelial differentiation when denuded AM is used as substrates. 20 The fact that the regenerated epithelial cells produced by the Method 1 were less stratified with poor polarity in the present study may be related to the above-mentioned notion.…”
Section: Discussionmentioning
confidence: 99%
“…34 Although the exact mechanism has not been fully elucidated, the 3T3 fibroblast culture system has successfully applied in the limbal epithelial cell culture. [35][36][37][38] Gruenterich et al demonstrated that the addition of 3T3 feeder cells in their cultivation system may be beneficial for preventing limbal epithelial differentiation when denuded AM is used as substrates. 20 The fact that the regenerated epithelial cells produced by the Method 1 were less stratified with poor polarity in the present study may be related to the above-mentioned notion.…”
Section: Discussionmentioning
confidence: 99%
“…The variability in integrin staining has been very well profiled across human corneal epithelium (Schlotzer-Schrehard and Kruse, 2005). In the cornea, ␤1, ␤4, and ␣6 integrins have been implicated in adhesion to the basement membrane, migration, and maintenance of a less differentiated phenotype (Watt, 2002;Wang et al, 2003;Zhou et al, 2004). Recently, Pajoohesh-Ganji et al (2005) identified a correlation between ␤1 and ␤4 localization and slow epithelial cell cycling in the mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…AM-based limbal explant culture has been shown to be a suitable culture system for the growth and maintenance of limbal explant outgrowth in a phenotypic characteristic similar to that of the in vivo limbal tissue (Wang et al, 2003). This culture system is therefore also suitable for studying the effect of growth factors on limbal epithelial cell growth and differentiation.…”
Section: Kgf Promotes Limbal Epithelial Outgrowth Through the Inductimentioning
confidence: 99%